Implementation of Institution's E-Learning Platform in Teaching Online at ITB AAS Indonesia - Tira Nur Fitria (STAI Miftahul Ula Nganjuk, 2021)
E-learning is one of impact of the development of information and communication technology (ICT) technology applied in education using the accessible website. The purpose of this research is to know the implementation of the Institution’s E-Learning Platform and to know the strengths and weaknesses of the implementation of the Institution’s E-Learning Platform of ITB AAS Indonesia. This research applies descriptive qualitative research. The result of the study shows that ITB AAS Indonesia began implementing e-learning to support face-to-face classrooms in the academic year 2020/2021. E-learning’s platform was made based on Learning Management System (LMS) that can be accessed at the website https://elearning.itbaas.ac.id/ Based on the implementation of the e-learning, there are several menus found such as “Home, Message, Teaching Schedule, Material, Task, My Comment, Lecturer’s Filter, Student’s Filter, Video Conference, and Logout”. But, during the observation of the implementation of the e-learning platform, there are several strengths and weaknesses. In strengths are 1) Multi Users, 2) Online Application. 3) Several menus available. In the weaknesses, 1. This application contains a lot of data, 2. This application’s design will only look good when opened by using a laptop or a computer, 3. In making the material, it can only be shared into the Study Program category- Semester, and it cannot be shared with each class. 4. There may be the possibility of sending the material incorrectly. 5. This application does not have the facilities for importing and exporting user data. 6. In making multiple-choice question assignments, there is still a manual import feature, 7. E-learning does not have a Video Conference feature, 8. In printing grades into a file pdf, an additional application is required. 9. E-learning cannot record learning and participants in a video. 10. This application does not have an installer version on the android/smartphone.